Peningkatan kecerahan dan daya rekat warna pada produk gerabah batik - Edi Eskak; Irfaina Rohana Salma; Hadi Sumarto (Institut Seni Indonesia Yogyakarta, 2017)
Application of batik techniques for decoration making on pottery products results in unique decorative motifs. Decorative motifs are formed by the process of color blocking using a substance called ‘malam’ (batik wax) on the surface of pottery, but the resulted colors are less bright. The adhesiveness of colors on the surface of pottery are also less strong. The purpose of this study is to optimize materials and batik pottery production process to improve the brightness and adhesion of the colors. Methods used are: (1) selection of pottery, (2) designing of motifs, (3) penyantingan/batik making, (4) staining (5) pelorodan / wax cleaning, (6) finishing, and (7) testing of fastness. The results show that the use of colorants rapid and naphthol produces brighter colors. The increasing color brightness is achieved with the initial step of selecting light colored pottery and completed with a final coating of transparent paint. Tests were performed on color resistancy to rubbing and midday direct light, with score ranging 1 - 5. The testing color resistancy to dry and wet rubbing results in a score of 3-4 (good enough). Color resistancy to direct midday light gets 4 (good). Brightness and fastness (strong adhesion) to transparently painted colors obtain a score of 5 (very good).Keywords: Increase of brightness, color adhesion, batik pottery